2019
DOI: 10.1055/s-0039-1693480
|View full text |Cite
|
Sign up to set email alerts
|

Does Robotic-Assisted Total Hip Arthroplasty Improve Accuracy of Cup Positioning?

Abstract: Acetabular component malpositioning is a frequent cause of complications in total hip arthroplasty including instability, increased wear, osteolysis, impingement, and revision surgery. Recently, robotics and navigation have been introduced to improve cup positioning in total hip arthroplasty. The purpose of this study was to compare the accuracy of postoperative acetabular component positioning using MAKO robotic-assisted versus manual acetabular component placement. A consecutive series of 100 total hip repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(22 reference statements)
0
3
0
1
Order By: Relevance
“…Lawson et al. 50,53 demonstrated statistically significant improvement in acetabular component positioning placed within 5° of the target alignment with the use of robotic guidance compared to standard techniques in a case series of 100 patients. Illgen et al.…”
Section: Robotic Assisted Surgerymentioning
confidence: 98%
See 1 more Smart Citation
“…Lawson et al. 50,53 demonstrated statistically significant improvement in acetabular component positioning placed within 5° of the target alignment with the use of robotic guidance compared to standard techniques in a case series of 100 patients. Illgen et al.…”
Section: Robotic Assisted Surgerymentioning
confidence: 98%
“…There is good evidence that robotic assisted surgery can help to improve implant positioning accuracy compared to manual placement in both hip and knee arthroplasty surgery. Lawson et al 50,53 demonstrated statistically significant improvement in acetabular component positioning placed within 5 of the target alignment with the use of robotic guidance compared to standard techniques in a case series of 100 patients. Illgen et al 51,54 found similar improvement in acetabular component placement for total hip arthroplasty accuracy using robotic assistance compared to manual placement.…”
Section: Robotic Assisted Surgerymentioning
confidence: 99%
“…Є вагомі докази того, що роботизована хірургія може допомогти покращити точність позиціонування імплантатів порівняно з ручним під час виконання тотального ендопротезування кульшового та колінного суглобів. Продемонстровано статистично значуще більшу кількість ацетабулярних компонентів, розміщених у межах 5° від цільового вирівнювання в разі використання роботизованої навігації [45]. Аналогічні результати отримано внаслідок спостереження за 300 пацієнтами, 100 з яких операцію тотального ендопротезування кульшового суглоба виконано з використанням роботизованої системи [46].…”
Section: адитивне виробництво й індивідуальні імплантатиunclassified
“…Orthopaedic robotic platforms accurately track markers rigidly attached to bones during joint replacement, allowing improved implant positioning [1,2]. There is currently no CAOS platform that uses markerless techniques to track bones and tools intraoperatively, although research shows some success in markerless tool tracking [3].…”
Section: Introductionmentioning
confidence: 99%